2015
DOI: 10.1111/ajo.12313
|View full text |Cite
|
Sign up to set email alerts
|

Why birthplace still matters for infants born before 32 weeks: Infant mortality associated with birth at 22–31 weeks’ gestation in non‐tertiary hospitals in Victoria over two decades

Abstract: Outborn livebirths at 22-31 weeks' gestation occur too frequently and are associated with a significantly increased risk of mortality. Strategies to reduce outborn livebirths are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
30
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 15 publications
9
30
2
1
Order By: Relevance
“…Overall, 58% of outborns died; the same proportion as in 2006–2009 23. Furthermore, the risk of mortality for outborn livebirths compared with inborn livebirths was marginally higher than we reported for the 2006–2009 cohort in Victoria (aOR 2.78 in 2010–2011 vs aOR 2.66 in 2006–2009) 23…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Overall, 58% of outborns died; the same proportion as in 2006–2009 23. Furthermore, the risk of mortality for outborn livebirths compared with inborn livebirths was marginally higher than we reported for the 2006–2009 cohort in Victoria (aOR 2.78 in 2010–2011 vs aOR 2.66 in 2006–2009) 23…”
Section: Discussioncontrasting
confidence: 48%
“…In Victoria, Australia, the gap between outborn and inborn mortality risks narrowed in the early 2000s; however, in 2006–2009, the gap widened again. Moreover, while inborn mortality declined, from 29% in 2001–2005 to 25% in 2006–2009, outborn infant mortality rose, from 51% to 58% 23. Given these trends, an updated investigation of outcomes for these infants was warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of death prior to discharge of 17% of outborn infants admitted to NICU is equivalent to other studies, which have shown outborn mortality rates of 16–27% for extremely preterm, preterm or very low birth weight (VLBW) outborn infants admitted to NICU …”
Section: Discussionmentioning
confidence: 50%
“…Those born in tertiary centres (inborn) have significantly better survival compared with preterm infants born outside of tertiary centres (outborn). [6][7][8][9][10][11][12][13][14] In Victoria, Australia, Boland et al demonstrated tripled odds of 1-year mortality among 23 to 27-week outborn infants compared with similar inborn infants born 1990-2009. 6 Centralisation of perinatal care, however, can lead to decreased exposure and therefore potential deskilling of peripheral health care staff who may still be required to infrequently manage preterm infants.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] In Victoria, Australia, Boland et al demonstrated tripled odds of 1-year mortality among 23 to 27-week outborn infants compared with similar inborn infants born 1990-2009. 6 Centralisation of perinatal care, however, can lead to decreased exposure and therefore potential deskilling of peripheral health care staff who may still be required to infrequently manage preterm infants. 15,16 In a non-tertiary hospital, preterm resuscitation may be challenging because of insufficient familiarity and inadequate advanced neonatal procedural skills (such as intubation, surfactant administration and umbilical vessel catheterisation).…”
mentioning
confidence: 99%